Cultural Awareness Through the Integrated PBL Model of Malay Cultural Ethnochemistry on Chemical Kinetics - Sukrisno, Sukrisno; Erna, Maria; Futra, Dedi; Paramastuti, Lujeng (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Culture, as a nation's invaluable asset, must continuously be introduced and preserved in alignment with the progress of time. Integrating cultural studies with scientific knowledge through education fosters the development of cultural awareness attitudes. A generation trained in cultural sensitivity will recognize the significance of heritage and innovate its presentation to suit contemporary developments. This study explores the use of a Problem-Based Learning (PBL) model integrated with the ethnochemistry of Malay culture—specifically utilizing traditional curd milk—in teaching chemical kinetics to enhance students' cultural awareness. The research employed a quasi-experimental method with a nonequivalent pre-test–post-test control group design, conducted at SMAN 2 Siak Hulu, Kampar, Riau Province, involving Grade XI Science students. Cultural awareness attitudes were assessed using indicators adapted from Wunderle, including data and information gathering, cultural consideration, cultural knowledge, cultural understanding, and cultural competence. The results demonstrated that the experimental group achieved an average cultural awareness score of 81.85 (categorized as Very Good), whereas the control group attained an average of 60.84 (Fairly Good). The learning model contributed significantly to enhancing cultural awareness attitudes, with a contribution rate of 56.1%. These findings suggest that integrating ethnochemistry within PBL effectively cultivates both scientific and cultural competencies in students.Keywords: cultural awareness, ethnochemistry, malay culture, PBL